INTENSITAS KOMUNIKASI TOKOH PUBLIK MELALUI PENDEKATAN HUBUNGAN KEKERABATAN UNTUK MENCEGAH PENYIMPANGAN SOSIAL - Adi, Dodot Sapto; Mariani, Ana (Universitas Merdeka Malang, 2017)
AbstractThis article is intended to provide a description of research results on the intensity of public figure communication through the approach of familial relationships to prevent social deviation. This study is a literature review study or literature study based on some previous research results by combining factual analysis. The results of this study can reveal the intensity of communication public figures are able to prevent and cope with social impediment in a social group. Where the heaviest of deviations is labeling which is the cause and effect of the explanation itself. Social deviation is examined from two aspects namely lifestyle and culture in social groups. The intensity of communication of public figures always reflects the closeness of the relationship between the elements of the system within the society, and is able to contribute through efforts to improve the existing conditions in the normative state. The higher the intensity of communicating, the higher the togetherness is created through new forms of agreement. The main determinant is the intensity of communication by public figures and communication approaches based on kinship relationships. Key Words: Communication Intensity, Public Figure, Kinship Relations and Social Diversity.DOI :Â https://doi.org/10.26905/nomosleca.v3i1.1482